Cost utility modeling of early vs late total knee replacement in osteoarthritis patients. Issue 12 (December 2016) - Mari, K.; Dégieux, P.; Mistretta, F.; Guillemin, F.; Richette, P.
Summary: Given the dramatic increase in the number of total knee replacement (TKR) surgeries in developed countries, the issue of the best time for surgery needs to be addressed from an economic perspective. Objective: To assess, from the perspective of the healthcare payer, the cost-utility of two surgical strategies in which knee replacement is performed at the early or late stage of the disease in patients with knee osteoarthritis (OA). Design: Patient data and evidence from published literature on economic costs and outcomes in OA, including utilities, non-pharmacological, pharmacological and surgical options, combined with population life tables were entered in a Markov model of OA. The model represented the lifetime experience of a cohort of patients following their therapeutic management, discounting costs (euros) and utilities (quality-adjusted life-years) at 4% annually. Results: In the base-case scenario, early TKR cost €6, 624 more than late TKR (€76, 223 vs €69, 599) with a 0.15 gain in QALYs (18.675 vs 18.524). This yielded an incremental cost-utility ratio (ICUR) of 43, 631 €/QALY. Sensitivity analyses of the most influential uncertain parameters were performed and did not modify the direction of the conclusions: early TKR cost between €3, 655 and €7, 194 more than late TKR with a gain in QALYs between 0.15 and 0.39. The ICUR ranged from 17, 131 €/QALY to 48, 241 €/QALY. Conclusion: Our data do not support the early TKR strategy over the late TKR strategy in knee OA patients from a medico-economic perspective.